Changing the Marriage Equation - Deborah A. Widiss (Washington University Law Review, 2012)
This Article brings together legal, historical, and social science research to analyze how couples allocate income-producing and domestic responsibilities. It develops a framework—what I call the “marriage equation”—that shows how sex-based classifications, (non-sex-specific) substantive marriage law, and gender norms interrelate to shape these choices. The marriage equation has changed over time, both reflecting and engendering societal preferences regarding the optimal allocation of breadwinning and caretaking responsibilities. Until fifty years ago, sex-based classifications in family and employment law aligned with gender norms to enforce an ideology of separate spheres for men and women. The groundbreaking sex discrimination cases of the 1970s ended legal distinctions between the duties of husbands and wives but left largely in place both gender norms and substantive rights within marriage, tax, and benefits law that encourage specialization into breadwinning and caregiving roles. Thus, contrary to popular conception, the modern marriage equation does not actually promote equal sharing of these responsibilities. Rather, it still encourages specialization, although the law is now formally agnostic about which spouse plays which role. The vast majority of different-sex couples still follow to some extent traditional gender roles. A body of emerging social science research suggests that same-sex couples typically allocate these responsibilities more equally than different-sex couples. But claims that same-sex couples may therefore serve as a model for different-sex couples improperly ignore that the data sets in these studies predate legal marriage for same-sex couples. By permitting disaggregation of the marriage equation to gauge more accurately the relative significance of sex, gender norms, and substantive marriage law, the new reality of same-sex marriage can serve as a natural experiment that should inform both study design and policy reform.
Keywords: Equal protection; Gender equality; Same-sex marriage; Defense of Marriage Act of 1996; United States